Characterization of stress-strain state in gas turbine engine compressor disc taking into account damage accumulation - Natalia V Boychenko; Ivan Ishtyryakov (Fracture and Structural Integrity)
The stress-strain state analysis of the gas turbine engine compressor disk was carried out taking into account damage accumulation under various loading conditions in the temperature range.